Pengaruh Model Flipped Classroom Terhadap Hasil Belajar Bahasa Indonesia Siswa Kelas IV SDN Bahagia 06 - Erika Paulina; Lelly Qodariah (Universitas Negeri Makassar, 2022)
The purpose of this study is to analyze, test and find out whether or not there is an influence of the Flipped Classroom model on the learning outcomes of Indonesian grade IV students of SDN Bahagia 06. The timing of this research is even in the 2021/2022 school year. The study population involved all students of SDN Bahagia 06, sampling in this study using the Cluster Random Sampling technique. With a study sample of 72 students. The students of class IV-B as an experimental class consist of 36 students and the students of class IV C as a control class consist of 36 students. This method uses the methode Quasi Experimental Design with a Posttest-Only Control Group Design. The analysis technique in this study is in the form of descriptive analysis and inferential analysis. The results of the hypothesis test in this study showed 2.36440897 > 1.66757228, then H1 was accepted. With this, it can be proven that there is an influence of the use of the Flipped Classroom model on the learning outcomes of Indonesian grade IV students of SDN Bahagia 06.